PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KINERJA KARWAYAN PADA PT BHUMYAMCA SEKAWAN - Muhamad Ridho Kurnianto; Imam Muhtadin (Media Riset Bisnis Manajemen Akuntansi, 2025)
This study aims to analyze the extent to which leadership style and work motivation influence employee performance at PT Bhumyamca Sekawan. Employee performance is a critical element in achieving organizational goals and is affected by various factors, including the leadership approach adopted and the level of individual work motivation. The research employed a quantitative method with an associative approach. Data were collected through the distribution of questionnaires to employees and analyzed using multiple linear regression techniques.The analysis results indicate that: (1) Leadership style has a positive and significant influence on employee performance, as evidenced by a t-value of 2.848, which is greater than the t-table value of 2.000, and a significance value of 0.007, which is less than 0.05. (2) Work motivation also has a positive and significant impact on performance, with a t-value of 2.813 t-table 2.000 and a significance value of 0.006 0.05. (3) Simultaneously, leadership style and work motivation significantly affect employee performance, as indicated by an F-value of 29.189, which exceeds the F-table value of 3.11, and a significance level of 0.000 0.05. Keywords : Leadership Style, Work Motivation, Employee Performance